Preparation method and application of PEDOT: PSS flexible thermoelectric film

The PEDOT:PSS flexible thermoelectric film was prepared by laser treatment and ammonia atmosphere treatment, which solved the problem of low preparation efficiency and difficulty in combining high conductivity and Seebeck coefficient in the prior art, and achieved high thermoelectric performance and good stability .

CN119497555APending Publication Date: 2025-02-21FOSHAN XIANHU LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411401357.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing organic thermoelectric films have low preparation efficiency and are difficult to have high conductivity and Seebeck coefficient.

Method used

PEDOT:PSS flexible thermoelectric film was prepared by laser treatment and ammonia atmosphere treatment. Laser treatment improves carrier transport capacity by destroying the insulated PSS chain; ammonia water atmosphere treatment increases the Seebeck coefficient by providing electron and dedoping reactions.

Benefits of technology

Improves the thermoelectric properties of PEDOT:PSS flexible thermoelectric films, combine high conductivity and Seebeck coefficient, and has excellent mechanical and environmental stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497555A_ABST
    Figure CN119497555A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrothermal films, and discloses a preparation method and application of a PEDOT: PSS flexible thermoelectric film. The preparation method comprises the following steps: carrying out laser irradiation and ammonia water atmosphere treatment on a PEDOT: PSS thin film to prepare the PEDOT: PSS flexible thermoelectric thin film. According to the preparation method of the PEDOT: PSS flexible thermoelectric thin film, the carrier concentration is greatly improved through first-step laser treatment, meanwhile, the conductive network structure is optimized, and the conductivity is greatly improved; after the second step of ammonia water atmosphere treatment, ammonia gas provides electrons for the surface of PEDOT to trigger a dedoping reaction, so that the Seebeck coefficient is increased; the PEDOT: PSS flexible thermoelectric thin film obtained by the invention has relatively high conductivity and Seebeck coefficient, and also has a relatively high power factor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electric heating films, and in particular relates to a preparation method and application of a PEDOT:PSS flexible thermoelectric film. Background Art

[0002] Thermoelectric materials are a new type of functional material that achieves direct conversion between heat and electricity through carrier migration inside solids. Because of their small size, quiet operation and no polluting gas, their potential applications in thermoelectric power generation and refrigeration have attracted widespread attention from researchers. Compared with inorganic thermoelectric materials, organic thermoelectric materials have the advantages of low production cost, strong controllability and wide application range. Organic thermoelectric materials refer to conductive polymers with conjugated main chain structures, which usually have unique advantages, including good mechanical flexibility, light weight, low cost, abundant materials, low toxicity or non-toxicity, etc. Most importantly, the thermal conductivity of organic thermoelectric materials is at least one order of magnitude lower than that of most inorganic semiconductors and semimetals. Considering the significant impact of the thermal conductivity term on the overall material figure of merit, the inherent low thermal conductivity of polymer materials is crucial to optimize their thermoelectric performance.

[0003] The existing organic thermoelectric thin films have a low preparation efficiency, and the prepared thin films are difficult to have both high electrical conductivity and Seebeck coefficient.

[0004] Therefore, there is an urgent need to provide a film with high preparation efficiency and high electrical conductivity and Seebeck coefficient. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a preparation method and application of a PEDOT:PSS flexible thermoelectric film.

[0006] PEDOT:PSS is a high-conductivity polymer composed of two substances, PEDOT (polymer of 3,4-ethylenedioxythiophene monomer) and PSS (polystyrene sulfonate). The interaction between these two substances can greatly improve the solubility of PEDOT. In order to improve charge transport and precisely control the doping level. The present invention proposes a method for preparing PEDOT:PSS flexible thermoelectric film using laser treatment and ammonia atmosphere treatment. This method can improve the thermoelectric properties of PEDOT:PSS flexible thermoelectric film, while having high electrical conductivity and Seebeck coefficient, and further has excellent mechanical and environmental stability. The method of optimizing the thermoelectric properties of laser-treated polymer films using ammonia atmosphere in the present invention has great potential in manufacturing high-efficiency and low-cost thermoelectric devices.

[0007] A first aspect of the present invention provides a method for preparing a PEDOT:PSS flexible thermoelectric film.

[0008] Specifically, a method for preparing a PEDOT:PSS flexible thermoelectric film comprises the following steps:

[0009] The PEDOT:PSS film is subjected to laser irradiation and ammonia atmosphere treatment to obtain the PEDOT:PSS flexible thermoelectric film.

[0010] Preferably, the process parameters of the laser irradiation are: laser wavelength is 1000-1030nm, scanning interval is 5-7μm, pulse width is 250-260fs, processing speed is 280-300mm s -1 , repetition rate is 180-200kHz, laser power density is 56-58.08mJ cm -2 .

[0011] Further preferably, the process parameters of the laser irradiation are: laser wavelength is 1030nm, scanning interval is 7μm, pulse width is 260fs, processing speed is 300mm s -1 , repetition rate is 200kHz, laser power density is 58.08mJ cm -2 (The corresponding laser power is 58mW).

[0012] Preferably, the concentration of ammonia in the ammonia atmosphere treatment is 0.01-0.4 mol L -1 , for example, 0.01 molL -1 , 0.1 mol L -1 , 0.2 mol L -1 , 0.3 mol L -1 , 0.4 mol L -1 , preferably 0.3 mol L -1 .

[0013] Preferably, the preparation method comprises the following steps:

[0014] (1) coating a PEDOT:PSS aqueous solution on a substrate to obtain a PEDOT:PSS film;

[0015] (2) irradiating the PEDOT:PSS film obtained in step (1) with a laser;

[0016] (3) The PEDOT:PSS film obtained in step (2) is then treated with an ammonia atmosphere to obtain the PEDOT:PSS flexible thermoelectric film.

[0017] Preferably, in step (1), the mass fraction of the PEDOT:PSS aqueous solution is 0.5-1.5%, more preferably 1-1.3%.

[0018] Preferably, in the PEDOT:PSS aqueous solution, the mass ratio of PEDOT to PSS is 1:(0.1-2).

[0019] Preferably, in step (1), the substrate is a PET (polyethylene terephthalate) substrate.

[0020] Preferably, in step (2), the laser is a pulsed femtosecond laser.

[0021] Preferably, the specific process of step (3) is: fix the PEDOT:PSS film obtained in step (2) together with the substrate on the experimental device frame, place the experimental device frame containing the PEDOT:PSS film obtained in step (2) upright in a sealed glass bottle, add ammonia water of different volume molar concentrations into the glass bottle, then put the glass bottle into an oven for heating treatment, and then take it out for cleaning to obtain the PEDOT:PSS flexible thermoelectric film.

[0022] Preferably, 3-5 mL of aqueous ammonia with different molar concentrations is added.

[0023] Preferably, the temperature of the oven is 55-60° C., and the treatment time is 1-60 minutes. More preferably, the temperature of the oven is 55-60° C., and the treatment time is 30-60 minutes.

[0024] Preferably, in step (3), the concentration of aqueous ammonia is 0.01-0.4 mol L -1 , for example, 0.01 mol L -1 , 0.1 mol L -1 , 0.2 mol L -1 , 0.3 mol L -1 , 0.4 mol L -1 , preferably 0.3 mol L -1 .

[0025] Preferably, in step (3), after the PEDOT:PSS film is treated with an ammonia atmosphere, deionized water is dropped on the PEDOT:PSS film to completely cover the surface of the PEDOT:PSS film, spin-coated to clean the film, and then dried.

[0026] Preferably, the spin coating speed is 1500-2000 rpm and the time is 10-20 s.

[0027] Preferably, the drying temperature is 70-80°C and the drying time is 10-15 minutes.

[0028] The present invention provides a PEDOT:PSS flexible thermoelectric film with high thermoelectric performance, which is prepared by sequentially performing femtosecond laser irradiation and ammonia atmosphere treatment, and the obtained PEDOT:PSS film has both high electrical conductivity and Seebeck coefficient. There are two factors that affect the electrical conductivity of the PEDOT:PSS film, one is the carrier concentration (oxidation level), and the other is the conductive structure. In the first step of laser treatment, the laser energy destroys the insulating PSS chain wrapped with PEDOT under the action of the thermal process, causing it to break and decompose, exposing the conductive PEDOT area, increasing the contact between the conductive chains, and improving the carrier transport capacity. At the same time, the PSS chain constraint is lost, and the rigid PEDOT chain conformation changes from a benzene-like type to a quinone-like type, which promotes the extension of the conjugated chain. Under the action of light stamping, the impact pressure of the order of GPa effectively reduces the π-π stacking distance of PEDOT, and increases the crystallinity of the film, the polymer structure region is ordered, and the electrical conductivity of the PEDOT:PSS film is improved. After the second step of ammonia atmosphere treatment, ammonia provides electrons to the PEDOT surface, triggering the dedoping reaction, thereby increasing the Seebeck coefficient; at the same time, NH 4 + With PSS - The combination weakens the interaction between PEDOT and PSS, resulting in a change in the polymer conformation. Femtosecond laser treatment can promote better ammonia atmosphere treatment, that is, femtosecond laser treatment of the film exposes more PEDOT areas on the film surface, which is conducive to the fine control of the PEDOT dedoping level by the ammonia atmosphere. Ammonia atmosphere treatment can also repair the damage to the film after femtosecond laser treatment, causing the film to undergo a self-healing process.

[0029] A second aspect of the present invention provides a PEDOT:PSS flexible thermoelectric film.

[0030] Specifically, a PEDOT:PSS flexible thermoelectric film is prepared by the above preparation method.

[0031] The third aspect of the present invention provides an application of the above-mentioned method for preparing a PEDOT:PSS flexible thermoelectric film.

[0032] The application of the preparation method of the above-mentioned PEDOT:PSS flexible thermoelectric film in the preparation of thermoelectric devices.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0034] (1) The present invention provides a method for preparing a PEDOT:PSS flexible thermoelectric film. The first step is laser treatment, which greatly increases the carrier concentration and optimizes the conductive network structure, thereby greatly improving the conductivity. After the second step of ammonia atmosphere treatment, ammonia provides electrons to the PEDOT surface, triggering a dedoping reaction, thereby increasing the Seebeck coefficient. The PEDOT:PSS flexible thermoelectric film obtained by the present invention has both high electrical conductivity and Seebeck coefficient, and also has a high power factor.

[0035] (2) The present invention obtains a high thermoelectric performance PEDOT:PSS flexible thermoelectric film through two steps of pulsed laser irradiation and ammonia atmosphere treatment. The preparation method is simple and has the advantages of simple and safe operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the process of preparing a PEDOT:PSS flexible thermoelectric film by a two-step method of femtosecond laser irradiation and ammonia atmosphere treatment in Example 1 of the present invention;

[0037] Figure 2 The thermoelectric properties of the PEDOT:PSS flexible thermoelectric films prepared at different ammonia concentrations in the embodiments of the present invention;

[0038] Figure 3 The thermoelectric performance of the PEDOT:PSS flexible thermoelectric film prepared in the embodiment of the present invention under the atmosphere of 0.3M ammonia concentration for different time periods;

[0039] Figure 4 The environmental stability of the PEDOT:PSS flexible thermoelectric film prepared in Example 8 of the present invention. DETAILED DESCRIPTION

[0040] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0041] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0042] Example 1: Preparation of PEDOT:PSS flexible thermoelectric film

[0043] A method for preparing a PEDOT:PSS flexible thermoelectric film comprises the following steps:

[0044] Step 1: Select a 200 μm thick PET substrate, ultrasonically clean the cut substrate (4×14 mm) with ethanol and deionized water for 15 minutes, and then dry it in an oven at 70°C for 1 hour to obtain a clean PET substrate;

[0045] Step 2: The PET substrate obtained in step 1 was irradiated with a UV cleaning machine for 15 minutes, taken out and placed on a hot plate at 60°C, 40 μL of a PEDOT:PSS aqueous solution (Herri PH1000) was spin-coated on the flexible substrate to cover the upper surface of the PET substrate, and then dried on the hot plate for 45 minutes (i.e., annealing) to obtain a PEDOT:PSS film with a uniform surface;

[0046] Step 3: Femtosecond laser irradiation: Place the PEDOT:PSS film obtained in step 2 on the galvanometer processing platform, turn on the femtosecond laser, the wavelength of the femtosecond laser used is 1030nm, the repetition frequency is 200kHz, the pulse width is 260fs, the laser power is fixed at 58mW, and the surface of the PEDOT:PSS film is irradiated at a scanning speed of 300mm / s and a scanning interval of 7μm. After laser annealing is completed, take out the film;

[0047] Step 4: Ammonia atmosphere treatment: Take out the PEDOT:PSS film after femtosecond laser annealing in step 3, stick the double-sided tape on one side of the PEDOT:PSS film substrate, and then fix the laser-treated PEDOT:PSS film and the substrate on the experimental device frame. Place the experimental device frame with the PEDOT:PSS film upright in another sealed glass bottle, and add 5 mL of the 0.01 mol L -1 ammonia water, and then put the glass bottle into an oven to heat it. The temperature of the oven is 60°C and the heating time is 60 minutes;

[0048] Step 5: Use a pipette to take 100 μL of deionized water and drop it on the PEDOT:PSS film treated in step 4, and completely cover the surface of the PEDOT:PSS film with deionized water. Then, place the PEDOT:PSS film on a spin coater and spin coat it at 2000 rpm for 20 seconds to remove the aqueous solution on the surface of the film.

[0049] Step 6: Remove the film after spin coating and place it on a hot plate at 80°C to dry for 15 minutes. After drying, the PEDOT:PSS flexible thermoelectric film is obtained.

[0050] Example 2

[0051] Compared with Example 1, the only difference in Example 2 is that the concentration of ammonia water used in step 4 is 0.3 mol L -1 , the rest of the process is the same as in Example 1.

[0052] Example 3

[0053] Compared with Example 1, the only difference in Example 3 is that the concentration of ammonia water used in step 4 is 0.1 mol L -1 , the rest of the process is the same as in Example 1.

[0054] Example 4

[0055] Compared with Example 1, the only difference in Example 4 is that the concentration of ammonia water used in step 4 is 0.2 mol L -1 , the rest of the process is the same as in Example 1.

[0056] Example 5

[0057] Compared with Example 1, the only difference in Example 5 is that the concentration of ammonia water used in step 4 is 0.4 mol L -1 , the rest of the process is the same as in Example 1.

[0058] Example 6

[0059] Compared with Example 2, the only difference in Example 6 is that the heating treatment time in step 4 is 15 minutes, and the rest of the process is the same as Example 2.

[0060] Example 7

[0061] Compared with Example 2, the only difference in Example 7 is that the heating treatment time in step 4 is 30 minutes, and the rest of the process is the same as Example 2.

[0062] Example 8

[0063] Compared with Example 2, the only difference in Example 8 is that the heating treatment time in step 4 is 45 minutes, and the rest of the process is the same as Example 2.

[0064] Comparative Example 1

[0065] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 does not undergo the ammonia atmosphere treatment in step 4, and the rest of the process is the same as that of Example 1.

[0066] Product effect testing

[0067] Figure 1 Schematic diagram of the process of preparing PEDOT:PSS flexible thermoelectric film by two-step method of femtosecond laser irradiation and ammonia atmosphere treatment in Example 1 of the present invention; Figure 1 It can be seen that the process of preparing the PEDOT:PSS flexible thermoelectric film of the present invention mainly involves femtosecond laser irradiation and ammonia atmosphere treatment.

[0068] Figure 2The thermoelectric properties of the PEDOT:PSS flexible thermoelectric films prepared at different ammonia concentrations in the embodiments of the present invention; Figure 2 “(a)” corresponds to the electrical conductivity of the PEDOT:PSS flexible thermoelectric film, “(b)” corresponds to the Seebeck coefficient of the PEDOT:PSS flexible thermoelectric film, and “(c)” corresponds to the power factor of the PEDOT:PSS flexible thermoelectric film.

[0069] Figure 3 The thermoelectric performance of the PEDOT:PSS flexible thermoelectric film prepared in an embodiment of the present invention by treating it in an atmosphere of 0.3M ammonia concentration for different time periods. Figure 3 “(a)” corresponds to the electrical conductivity of the PEDOT:PSS flexible thermoelectric film, “(b)” corresponds to the Seebeck coefficient of the PEDOT:PSS flexible thermoelectric film, and “(c)” corresponds to the power factor of the PEDOT:PSS flexible thermoelectric film.

[0070] Figure 4 The environmental stability of the PEDOT:PSS flexible thermoelectric film prepared in Example 8 of the present invention. Figure 4 "(a)" corresponds to the change of the electrical conductivity of the PEDOT:PSS flexible thermoelectric film over time, "(b)" corresponds to the change of the Seebeck coefficient of the PEDOT:PSS flexible thermoelectric film over time, and "(c)" corresponds to the change of the power factor of the PEDOT:PSS flexible thermoelectric film over time.

[0071] The figure shows that the conductivity of the original PEDOT:PSS film is 0.1-1S cm -1 , the Seebeck coefficient is ~16μV / K. After step three femtosecond laser annealing, the conductivity of the PEDOT:PSS flexible thermoelectric film reaches 803S / cm( Figure 2 ), the Seebeck coefficient is ~15μV / K( Figure 2 ), power factor 18.81μW / m / K 2 .

[0072] The laser-treated PEDOT:PSS film was treated with ammonia water of different concentrations. When the ammonia concentration increased from 0.01M to 0.4M, the Seebeck coefficient increased from the original 15μV K -1 Increase to a current of 26.85μV K -1 , but the conductivity dropped rapidly from the original 836.23S cm -1 Down to 251S cm -1 ( Figure 2 ). In Example 2, the optimal ammonia concentration is 0.3M and the optimal power factor is 24.16μW·m -1 ·K -2Different heating treatment times have different effects on thermoelectric properties, so the laser annealed film was treated in an atmosphere of 0.3M ammonia concentration for 15min, 30min, 45min, and 60min. The Seebeck coefficient is not sensitive to long-term post-treatment in an ammonia atmosphere. The Seebeck coefficient of the film is stable at 26.39μV K -1 , but the conductivity of the film is extremely sensitive to the time of atmosphere treatment ( Figure 3 ). Before the ammonia atmosphere treatment, it was 836.23S cm -1 After 60 min of atmosphere treatment, it dropped to about 347 S cm -1 ( Figure 3 ), and it was also found that the effect of ammonia atmosphere treatment time on the conductivity of the film was not linear. The conductivity first decreased and then increased with the ammonia atmosphere treatment time, and then decreased again after a period of time. In Example 8, the best effect was obtained when the atmosphere was treated for 45 minutes at a concentration of 0.3M ammonia, and the film conductivity was 26.15μV K -1 , conductivity is 413.19Scm -1 , the best power factor is 28.24μW·m -1 ·K -2 ( Figure 3 ).

[0073] After 30 days, the conductivity, Seebeck coefficient and power factor of the PEDOT:PSS flexible thermoelectric film prepared in Example 8 did not change significantly ( Figure 4 , Figure 4 The ordinate in Figure (a) represents the ratio of conductivity at a certain time to the initial conductivity, and the abscissa "Time (day)" represents time; Figure 4 The vertical axis in Figure (b) represents the ratio of the Seebeck coefficient at a certain time to the initial Seebeck coefficient. Figure 4 The vertical axis in Figure (c) represents the ratio of the power factor at a certain time to the initial power factor), indicating that its stability is good.

[0074] The conductivity of the film prepared in Comparative Example 1 is 836.23 S cm -1 , Seebeck coefficient is 15.2μV K -1 , the best power factor is 18.81μW·m -1 ·K -2 .

[0075] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a PEDOT:PSS flexible thermoelectric film, characterized in that: The following steps are involved: The PEDOT:PSS film is subjected to laser irradiation and ammonia atmosphere treatment to obtain the PEDOT:PSS flexible thermoelectric film.

2. The preparation method according to claim 1, characterized in that: The process parameters of the laser irradiation are: laser wavelength is 1000-1030nm, scanning interval is 5-7μm, pulse width is 250-260fs, processing speed is 280-300mm s -1 , repetition rate is 180-200kHz, laser power density is 56-58.08mJ cm -2 .

3. The preparation method according to claim 1, characterized in that: The concentration of ammonia in the ammonia atmosphere treatment is 0.01-0.4 mol L -1 .

4. The preparation method according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) coating a PEDOT:PSS aqueous solution on a substrate to obtain a PEDOT:PSS film; (2) irradiating the PEDOT:PSS film obtained in step (1) with a laser; (3) The PEDOT:PSS film obtained in step (2) is then treated with an ammonia atmosphere to obtain the PEDOT:PSS flexible thermoelectric film.

5. The preparation method according to claim 4, characterized in that: In step (1), the mass fraction of the PEDOT:PSS aqueous solution is 0.5-1.5%.

6. The preparation method according to claim 4, characterized in that: The specific process of step (3) is as follows: fix the PEDOT:PSS film obtained in step (2) together with the substrate on the experimental device frame, place the experimental device frame containing the PEDOT:PSS film obtained in step (2) upright in a sealed glass bottle, add ammonia water of different volume molar concentrations into the glass bottle, then put the glass bottle into an oven for heating treatment, and then take it out for cleaning to obtain the PEDOT:PSS flexible thermoelectric film.

7. The preparation method according to claim 6, characterized in that: The temperature of the oven is 55-60°C and the treatment time is 1-60 minutes.

8. The preparation method according to claim 6, characterized in that: In step (3), after the PEDOT:PSS film is treated with an ammonia atmosphere, deionized water is dropped on the PEDOT:PSS film to completely cover the surface of the PEDOT:PSS film, spin-coated to clean the film, and then dried.

9. A PEDOT:PSS flexible thermoelectric film, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the preparation method according to any one of claims 1 to 8 in the preparation of thermoelectric devices.